PENERAPAN METODE STAD BERBANTUAN MEDIA BERBASIS ANDROID UNTUK MENINGKATKAN KETERAMPILAN MEWAWANCARAI - Sukoco, Alun; Djuanda, Dadan; Maulana, Maulana (Jurnal Pena Ilmiah, 2019)
Indonesian has four language skills that must be have. One of the four skills is speaking. Many activitiescan be taught to improve speaking skills, one of them is interviewing activities. Early data indicates thatthere are problems in the interview activity. Based on this, these problems can be used as the basis ofclassroom action research (CAR), with the aim to correcting problems. To fix this, the Student TeamsAchievement Divisions (STAD) method assisted by an Android-based media in the form of anapplication is applied. The STAD is part of Cooperative Learning, which student groups characteristics.For the media, features are adapted to the STAD syntax, so it can help and attract student attention inlearning. This research was conducted in three cycles. In first cycle, students who pass the test just7 students equal to 24.1%. In second cycle, students who pass the test is 17 students equal to58.6%. In third cycle, students who pass the test is 26 students equal to 89.6%. Thus, it can beconcluded that STAD assisted by android-based media applications can improve studentlearning outcomes. It was found that there was an increasement in learning outcomes in each cycleand had reached the teachers target of more than 85%.